2018
DOI: 10.1111/vco.12415
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of contrast‐enhanced computed tomography for assessment of mandibular and medial retropharyngeal lymph node metastasis in dogs with oral and nasal cancer

Abstract: The diagnostic accuracy of contrast-enhanced CT for detection of cervical lymph node metastasis in dogs is unknown. The purpose of this retrospective, observational, diagnostic accuracy study was to assess the efficacy of CT for detection of mandibular and medial retropharyngeal lymph node metastasis in dogs. Histopathology of dogs with cancer of the head, CT and bilateral mandibular and medial retropharyngeal lymphadenectomy was reviewed. A single radiologist measured lymph nodes to derive short axis width an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 55 publications
5
69
2
1
Order By: Relevance
“…In addition, calculation of PSIL was significantly different between metastatic and non‐metastatic lymph nodes, showing that subjective assessment and quantitative analysis was reflective of histological results in this small population of dogs. This is in contrast to multiple other studies in dogs with head and neck tumours where more recent articles have indicated a lower level of sensitivity and specificity of imaging parameters such as apparent diffusion coefficient (ADC) values, contrast enhancement patterns and size for predicting presence of metastasis …”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…In addition, calculation of PSIL was significantly different between metastatic and non‐metastatic lymph nodes, showing that subjective assessment and quantitative analysis was reflective of histological results in this small population of dogs. This is in contrast to multiple other studies in dogs with head and neck tumours where more recent articles have indicated a lower level of sensitivity and specificity of imaging parameters such as apparent diffusion coefficient (ADC) values, contrast enhancement patterns and size for predicting presence of metastasis …”
Section: Discussioncontrasting
confidence: 70%
“…In one article regarding staging for oral melanomas in dogs, there was a reported sensitivity and specificity of 70% and 51%, respectively, for diagnosis of lymph node metastasis based on the size of the lymph node alone . Imaging characteristics of lymph nodes on CT for canine oral and nasal tumours have shown to have a sensitivity and specificity of 12.5% and 91.1% for the diagnosis of metastasis in another report . Non‐invasive methods of identifying lymph node metastasis is an on‐going area of research that continues to attract considerable attention …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CT is more sensitive than radiography for detecting pulmonary nodules and is becoming the imaging method of choice for assessment of pulmonary metastasis, especially for highly malignant tumours such as osteosarcoma and melanoma (Armbrust et al 2012); in oral malignant melanoma, CT can also be used to assess mandibular and retropharyngeal lymphadenopathy. However, even with contrast enhancement, the sensitivity of CT in detection of cervical lymph node metastasis is low and CT cannot be relied on alone for this purpose (Skinner et al 2018). On the other hand, CT is more sensitive than radiography for detection of mediastinal lymphadenopathy and would be the method of choice for assessment of an animal with a lung mass.…”
Section: Diagnostic Imagingmentioning
confidence: 99%
“…However, even with contrast enhancement, the sensitivity of CT in detection of cervical lymph node metastasis is low and CT cannot be relied on alone for this purpose (Skinner et al . ). On the other hand, CT is more sensitive than radiography for detection of mediastinal lymphadenopathy and would be the method of choice for assessment of an animal with a lung mass.…”
Section: Introductionmentioning
confidence: 97%